RIBOFLAVIN CONTENT IN EXTRACTS OF THREE VERBASCUM SPECIES - Grigorov, Maja; Sunarić, Slavica; Pavlović, Dragana (Archives of Pharmacy, 2023)
B complex vitamins possess numerous biological activities on the human body, skin, hair and nails. That is why their content in different plant extracts could be important for the assessment of the health effects of these products (1). Species from the genus Verbascum are well known for their anti-inflammatory, antimicrobial, antiseptic, sedative, diuretic, immunomodulatory and antiviral activities (2). The aim of our work was to determine riboflavin in different extracts of three Verbascum species. The flowers of Verbascum niveum (VN), Verbascum speciosum (VS) and Verbascum phlomoides (VP) were collected in the vicinity of Bosilegrad, and the extracts were prepared by percolation with two different solvents (ethanol 50% and distilled water). HPLC method with fluorescence detection was employed for detection and quantification with the application of an external standard. The results are presented in mg/g of dry extract. According to our results, riboflavin was detected in all tested extracts. The highest amount was found in the water extract of VS (1.25 mg/g), and the lowest content was determined in the ethanol extract of VS (0.49 mg/g). While the aqueous extract was richer than ethanol in plant species VS, in plant species VN and VP a higher content was determined in ethanol (0.90 mg/g and 0.84 mg/g) compared to water extracts (0.56 mg/g and 0.53 mg/g). Based on our results, we can conclude that these species are rich in riboflavin and that its amount varies depending on the plant species and the solvent for extraction used.